PERANAN KEPALA SEKOLAH SEBAGAI INOVATOR DI TAMAN KANAK-KANAK SE-KECAMATAN PAYUNG SEKAKI DAN SE-KECAMATAN SUKAJADI KOTA PEKANBARU - Handini, Elvira (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study has to determine the role of the headmasters as an innovator in kindergarten Payung Sekaki sub-district and sub-district Sukajadi Pekanbaru City. The population of this research 43 headmaster kindergarten sub-district Payung Sekaki and sub-district Sukajadi Pekanbaru City, and the samples of this study is to use a technique saturated sampling in which all members of the population sampled totaling 43 kindergarten headmasters. This research method is descriptive research methods to determine the value of an independent variable that is without comparison or combining with one another variable. This type of instrument used in this research is to use statements with Likert scale. Data analysis by using statistical analysis methods. The results of the study the role of headmasters in kindergarten Payung Sekaki sub-district and Sukasadi sub-district of Pekanbaru City obtained a score of 4520 with a percentage of 72.99% in the good category.Key word: Headmasters role as an innovator